Evaluation of the Top Structure at PT. Sam Kyung Jaya Busana Factory Building Based on P-M-M Ratio Capacity Value - Amhudo, Rasyiid Lathiif (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2022)
Factory buildings that have been erected or built and have been used in their daily lives by many people need a thorough structural evaluation. Evaluation of the structure is important because it involves the safety of the occupants in it. Factory Building PT. Samkyung Jaya Clothing is one of the areas where the existing structure has not been analyzed, the building is composed of gording elements, rafter beams, rafter columns, sloof beams and other supporting elements. Factory Building PT. Samkyung Jaya Clothing made of steel with BJ-37 quality, the main building plan measuring 150x90 meters, with a total height of 14.45 meters, rafters using castellated beam WF. 150x175x7x11, rafter columns use 4 types of shapes, and pedestal columns and foundations also have 4 types of shapes, as well as sloof beams there are 2 types, namely 400x200 and 300x150 millimeters. The analysis uses 2 types, namely conventional calculations and computations that use the ETABS V.20.0 program. The results of the evaluation using ETABS V.20.0 there are several points in the pedestal column that experienced warnings such as columns P1 and P2, column K1 also experienced the same thing, namely Column factored axial load exceeds Euler Force and Capacity ratio exceeds limit where the ratio range is 0.5 -1.518. The purlin cross section also experiences Capacity ratio exceeds where the ratio is more than one, namely 1.169 and 1.666. Added reinforcement is the main thing, which can use the jacketing or retrofitting method.